COVID-19 among cancer patients. What we know so far? - Peixoto, Renata D'Alpino; Lopes, Moises de Sousa Martins (Brazilian Journal of Oncology, 2020)
In December 2019, a novel coronavirus disease (COVID-19) emerged in Wuhan, a city in the Hubei, Province of China. It rapidly spread in an epidemic fashion throughout China, followed by rapid increasing number of cases in many countries throughout the world, including Brazil. It is expected that oncologic patients have an increased risk of COVID-19 infection with possible worse clinical outcomes. We aim at reviewing current evidence of COVID-19 disease among cancer patients.
Keywords: Coronavirus; Cancer survivors; Drug therapy